A multi-disciplinary workflow for characterising shale seals - Dewhurst, D.; Clennell, M.; Burgar, I.; Josh, M.; Sarout, J.; Delle Piane, C.; Esteban, L.; Pervukhina, Marina; Raven, M. (European Association of Geoscientists and Engineers, EAGE, 2012)
Evaluation of the various rock properties of shales has become more prevalent in recent years although our understanding of these properties and the links between them is still relatively embryonic. While thick shale sequences can form sealing units above hydrocarbon traps, intra-reservoir shales can form baffles to flow in both petroleum and groundwater contexts. High field and low field nuclear magnetic resonance were used to evaluate wettability of shales. Preserved shales show mineral dependent variations in surface affinity for oil versus water. Hydrophilic shales have a higher cation exchange capacity (e.g. shales rich in illitic and/or smectite), whereas kaolinitic mudrocks are potentially hydrophobic and can be wetted preferentially by oil, sometimes retaining oil on the mineral surfaces after further exposure to brines. Porosity and cation exchange capacity correlate well with strength properties and dielectric constant measurements on intact shales and pastes made from powdered shales show strong relationships between high frequency electrical properties, mineralogy, cation exchange capacity and mechanical strength. Calibrating wireline logs with laboratory measurements and the development of physics-based models allows the prediction of rock properties and extrapolation to the borehole scale.